2013
DOI: 10.1371/journal.pone.0067244
|View full text |Cite
|
Sign up to set email alerts
|

Active-State Models of Ternary GPCR Complexes: Determinants of Selective Receptor-G-Protein Coupling

Abstract: Based on the recently described crystal structure of the β2 adrenergic receptor - Gs-protein complex, we report the first molecular-dynamics simulations of ternary GPCR complexes designed to identify the selectivity determinants for receptor-G-protein binding. Long-term molecular dynamics simulations of agonist-bound β2AR-Gαs and D2R-Gαi complexes embedded in a hydrated bilayer environment and computational alanine-scanning mutagenesis identified distinct residues of the N-terminal region of intracellular loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 61 publications
9
62
0
Order By: Relevance
“…A similar interaction is observed in structures of inhibited G␣ subunits (76 -78) and in the context of the G␤␥ subunits (16,17) prompting an analogy to a "seatbelt" that prevents GDP release (16). Consistent with the role of this interaction in controlling nucleotide release, the distance between the closest Glu-43O⑀ and Arg-178N atoms lengthens under conditions that promote nucleotide exchange (75).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…A similar interaction is observed in structures of inhibited G␣ subunits (76 -78) and in the context of the G␤␥ subunits (16,17) prompting an analogy to a "seatbelt" that prevents GDP release (16). Consistent with the role of this interaction in controlling nucleotide release, the distance between the closest Glu-43O⑀ and Arg-178N atoms lengthens under conditions that promote nucleotide exchange (75).…”
Section: Discussionsupporting
confidence: 56%
“…Molecular dynamics simulations proposed that receptor recognition stabilizes the ␣N-␤1 junction and the ␤2-␤3 hairpin of the G␣ subunit (74,75), and fluorescence studies indeed revealed receptor-mediated changes in the solvent accessibility of these regions (7,72) (Fig. 9, orange).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A model for the G αi -protein was constructed, using a previously published model for active-state G i in complex with the D 2 dopaminergic receptor. 67 The D 2 -G αi ternary complex was aligned to the ADRB2-G αs complex and the BU72-μOR complex, followed by substituting the Nb9-8 with the G αi .…”
Section: μ-Opioid Receptormentioning
confidence: 99%
“…A structural model for the bradykinin B 2 receptor indicated the presence of the ionic lock and showed, in combination with mutational studies, its role for the stabilization of the inactive receptor state [11]. Kling et al [12] used an active-state homology model of the dopamine D 2 receptor-Gα i protein-complex. Their simulations revealed ligand-dependent conformational changes of the G protein binding epitopes that show substantial differences for full or partial agonist bound complexes.…”
Section: Receptor Functionalitymentioning
confidence: 99%